Reading Hamka's and Shihab's Interpretations of Jihad: Abdullah Saeed's Contextual Approach - Bakar, Abu; Mahzumi, Fikri; Zamzami, Mukhammad (Journal of Islamic Thought and Civilization, 2025)
Jihād has been a significant issue in Indonesia over the past two decades, often linked to terrorism, radicalism, and sectarian violence, purportedly in the name of Islam. The Qurʾān, as the primary source of guidance for Muslims, presents jihād both as a concept of communal warfare and an expression of personal piety. However, selective interpretations of jihād by certain groups have contributed to theological justifications for terrorist and extremist actions. This study examined and compared the Qurʾānic interpretations of jihād by two prominent Indonesian Islamic scholars, Haji Abdul Malik Karim Amrullah (1908–1981) and M. Quraish Shihab (1944–). Using Abdullah Saeed's contextual approach, this research analyzed the methodological, typological, and paradigmatic frameworks underpinning their interpretations. The findings suggested that both scholars emphasized the necessity to understand jihād verses within their historical and sociocultural context. In a contemporary context, jihād should be interpreted as an earnest “struggle in the cause of Allah” rather than a call for armed conflict against non-believers. This approach aligns with Saeed's view that the jihād verses have ethical and legal dimensions, addressing social, economic, and political challenges faced by the early Muslim community at the time of revelation rather than solely advocating for violence.